An analysis of stability on rock slope by changing water level - Jang, Hyong Doo (Korean Society for Rock Mechanics, 2010)
A quarry with 105 m height large cut slope was analyzed. Beside RMR and SMR methods, FLAC2D were adopted to analyze slope stability. As a result, slope of and a site had a possibility of failure. Wet slope showed low safety factor. Soil nailing was recommended to solve it. Since safety factor of slope largely depend on underground level, investigation for it seemed necessary.